2007
DOI: 10.1371/journal.pgen.0030135
|View full text |Cite
|
Sign up to set email alerts
|

Unbiased Gene Expression Analysis Implicates the huntingtin Polyglutamine Tract in Extra-mitochondrial Energy Metabolism

Abstract: The Huntington's disease (HD) CAG repeat, encoding a polymorphic glutamine tract in huntingtin, is inversely correlated with cellular energy level, with alleles over ∼37 repeats leading to the loss of striatal neurons. This early HD neuronal specificity can be modeled by respiratory chain inhibitor 3-nitropropionic acid (3-NP) and, like 3-NP, mutant huntingtin has been proposed to directly influence the mitochondrion, via interaction or decreased PGC-1α expression. We have tested this hypothesis by comparing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 60 publications
(63 reference statements)
4
54
0
Order By: Relevance
“…There is also some evidence that mHtt can impair cellular bioenergetics by affecting extra-mitochondrial pathways. 9,10 In addition, expression of mHtt in non-neuronal cells such as astrocytes may also exacerbate HD neuropathology. [11][12][13][14][15] Astrocytes regulate energy metabolism by providing neuronal mitochondria with energy substrates derived from glycolysis.…”
Section: Introductionmentioning
confidence: 99%
“…There is also some evidence that mHtt can impair cellular bioenergetics by affecting extra-mitochondrial pathways. 9,10 In addition, expression of mHtt in non-neuronal cells such as astrocytes may also exacerbate HD neuropathology. [11][12][13][14][15] Astrocytes regulate energy metabolism by providing neuronal mitochondria with energy substrates derived from glycolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Impairment of the ubiquitin-proteasome pathway has been reported in HD (Bennett et al, 2007). Transcriptional dysregulation has also been widely reported in HD (Cha, 2007) and specifically in the STHdh Q111/Q111 cells (Lee et al, 2007) and in the R6/2 mice (Crocker et al, 2006). We found that xCT mRNA expression is decreased in the STHdh Q111/Q111 cells (unpaired Student's t-test, t(7)=7.4, p<0.005; Mann-Whitney test, p<0.001) (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…133 Defects in extra-mitochondrial energy metabolism have been observed in mouse striatal models of HD. 134 In addition to the potential mitochondrial dysfunction via decreased MnSOD discussed in the previous section, reductions in important metabolites necessary for the tricarboxylic acid (TCA) cycle can also lead to reduced mitochondrial respiration and ATP production. One important enzyme that produces metabolites for the TCA cycle is pyruvate carboxylase.…”
Section: Energeticsmentioning
confidence: 99%
“…Of note, gene expression profiling data from a striatal model of HD implicated several genes in glucose metabolism as being altered in HD; in particular, expression of PCX (the gene which encodes PC) is elevated in an HD mutant line. 134 Thus, models of both HD and manganese deficiency in rodents result in increased PC expression or activity.…”
Section: Energeticsmentioning
confidence: 99%